A New Version of Inextensible Flows of Spacelike Curves with Timelike B2 in Minkowski Space-Time E14 - Körpinar, Talat; Turhan, Essin (My University, 2013)
In this paper, we study inextensible flows of spacelike curves with timelike B2 in the Minkowski space-time E14 We give necessary and sufficient conditions for this inextensible flows. We derive the evolution equations for this inextensible flows in the Minkowski space-time E14 © 2012 Foundation for Scientific Research and Technological Innovation.
Keywords: Fluid flow; Inextensible flows; Minkowski space-time; Moving frame